Hyperglycemia and Hyperlipidemia with Kidney or Liver Transplantation: A Review - John A. D’Elia; Larry A. Weinrauch (Biology, 2023)
Although solid organ transplantation in persons with diabetes mellitus is often associated with hyperglycemia, the risk of hyperlipidemia in all organ transplant recipients is often underestimated. The diagnosis of diabetes often predates transplantation; however, in a moderate percentage of allograft recipients, perioperative hyperglycemia occurs triggered by antirejection regimens. Post-transplant prescription of glucocorticoids, calcineurin inhibitors and mTOR inhibitors are associated with increased lipid concentrations. The existence of diabetes mellitus prior to or following a liver transplant is associated with shorter times of useful allograft function. A cycle involving Smad, TGF beta, m-TOR and toll-like receptors has been identified in the contribution of rejection and aging of allografts. Glucocorticoids (prednisone) and calcineurin inhibitors (cyclosporine and tacrolimus) induce hyperglycemia associated with insulin resistance. Azathioprine, mycophenolate and prednisone are associated with lipogenesis. mTOR inhibitors (rapamycin) are used to decrease doses of atherogenic agents used for immunosuppression. Post-transplant medication management must balance immune suppression and glucose and lipid control. Concerns regarding rejection often override those relative to systemic and organ vascular aging and survival. This review focuses attention on the underlying mechanism of relationships between glycemia/lipidemia control, transplant rejection and graft aging.